Effects of decursinol angelate on viability and apoptosis in PC-3 prostate cancer cells: In vitro study - Rahman, Zakaria A.; Hidayatullah, Furqan; Pratama, Putu KD.; Andhika, Dimas P.; Hakim, Lukman (Narra J, 2024)
Prostate cancer represents the predominant malignant neoplasm observed in the male population and ranks second in terms of mortality attributable to malignant neoplasm among men. Decursinol angelate (DA), derived from the plant Angelica gigas Nakai (AGN), has demonstrated anti-cancer effectiveness through the induction of intrinsic and extrinsic apoptosis pathways, inhibition of cancer cell proliferation, having anti-neovascularization, anti-inflammatory anti-oxidative activities and stimulating the immune process. The aim of this study was to determine the IC50 dose of DA on human prostate cancer cell line PC-3, as well as to assess its effects on cell viability and apoptosis. PC-3 cells were utilized in this study due to its hormonal therapy resistance characteristics. The treatment commenced with the determination of the IC50 of DA and cell viability using the CCK-8 method as a baseline dose. A combination with abiraterone acetate (AA) was performed using an escalated dose based on its IC50 to identify whether DA has a synergy with AA in decreasing PC-3 cell viability. Apoptosis levels were measured using flow cytometry. The research includes a control group (C) and three treatment groups: AA group, DA group, and DA+AA group. GraphPad Prism, SPSS version 25 and CompuSyn software were used for statistical analysis. This study reveals that the IC50 dose of DA is 13.63 µM. The decrease of PC-3 cell viability exposed to DA occurs in a dose-dependent manner. Additionally, PC-3 cell apoptosis is significantly increased in both the DA group and DA+AA compared to the control. Moreover, no difference in apoptosis level is noted between the DA and AA groups. Notably, there is a synergy between DA and AA, where a specific dose equal to one-fourth of the IC50 dose results in greater efficacy in reducing PC-3 cell viability compared to individual treatments of either DA or AA at the IC50 doses. This study demonstrates the potential of decursinol angelate as a single drug or combined with abiraterone acetate to reduce viability and increase apoptosis of castrate-resistant prostate cancer cells.